Luminescence of SiO₂ and GeO₂ crystals with rutile structure. Comparison with α-quartz crystals and relevant glasses (Review Article) - Trukhin, A.N. (Физика низких температур, 2016)
Luminescence properties of SiO₂ in different structural states are compared. Similar comparison is made for GeO₂. Rutile and α-quartz structures as well as glassy state of these materials are considered. Main results are that for α-quartz crystals the luminescence of self-trapped exciton is the general phenomenon that is absent in the crystal with rutile structure. In rutile structured SiO ₂ (stishovite) and GeO₂ (argutite) the main luminescence is due to a host material defect existing in as-received (as-grown) samples. The defect luminescence possesses specific two bands, one of which has a slow decay (for SiO₂ in the blue and for GeO₂, in green range) and another, a fast ultraviolet (UV) band (4.75 eV in SiO₂ and at 3 eV in GeO₂). In silica and germania glasses, the luminescence of self-trapped exciton coexists with defect luminescence. The latter also contains two bands: one in the visible range and another in the UV range. The defect luminescence of glasses was studied in details during last 60–70 years and is ascribed to oxygen deficient defects. Analogous defect luminescence in the corresponding pure nonirradiated crystals with α-quartz structure is absent. Only irradiation of a α-quartz crystal by energetic electron beam, γ-rays and neutrons provides defect luminescence analogous to glasses and crystals with rutile structure. Therefore, in glassy state the structure containing tetrahedron motifs is responsible for existence of self-trapped excitons and defects in octahedral motifs are responsible for oxygen deficient defects.